Prognostic value of pulse pressure after an acute coronary syndrome. (October 2018) - Harbaoui, Brahim; Nanchen, David; Lantelme, Pierre; Gencer, Baris; Heg, Dick; Klingenberg, Roland; Räber, Lorenz; Carballo, David; Matter, Christian M.; Windecker, Stephan; Mach, François; Rodondi, Nicolas; et al.
Abstract: Background and aims: Pulse pressure (PP) is a surrogate of aortic stiffness (AS) easily obtainable. The link between AS and cardio-vascular disease is documented, however, data regarding acute coronary syndrome (ACS) patients are scarce and contradictory. We aimed to assess the prognostic value of PP measured at admission, with regard to major adverse outcomes (all-cause mortality, recurrence of MI, and stroke), during the first year following an acute coronary syndrome (ACS). Methods: The SPUM–ACS project is a prospective cohort study of patients with ACS conducted in 4 Swiss University hospitals. Patients with no PP at admission or with severe clinical heart failure or cardiogenic shock were excluded. Cox regression analyses were performed to determine associations between PP and outcomes (all-cause mortality, recurrence of myocardial infarction (MI), and stroke). Three multivariate Cox regression models were adjusted for hemodynamic, cardiovascular, and non-cardiovascular confounders, added successively. Results: Of 5635 eligible patients, 5070 met the inclusion criteria. Mean patient age was 63 years (range: 54–72), 79.6% were male, and mean blood pressure and PP were 93.9 ± 15.6 and 54 ± 17 mmHg, respectively. Multivariate analyses confirmed the prognostic significance of PP for each 10-mmHg increase for the composite endpoint, hazard ratio (HR) 1.126 [1.051–1.206], p = 0.001; all-cause mortality, HR1.129 [1.013–1.260], p = 0.029; and recurrence of MI, HR1.206 [1.102–1.320], p < 0.001; but not for stroke, HR1.014[0.853–1.205]. Conclusions: PP measured at admission is a strong, independent prognostic marker predicting mortality and recurrence of MI after ACS. PP should be considered for the management of secondary prevention. Highlights: Pulse pressure (PP), a surrogate of aortic stiffness, is associated with cardiovascular disease in various populations. After an acute coronary syndrome (ACS), patients may exhibit a poor outcome despite a modern guideline-based management. PP measured at admission is a robust and independent prognostic marker after diagnosis of ACS. PP measurement could be critical to the development of new preventive strategies. PP measurement could be critical to optimize the use of existing ones.